OPTIMASI WEBSITE TOKO KERJA MENGGUNAKAN UJI PERFORMA GOOGLE PAGESPEED INSIGHTS - Wangsa, Frans Junior; Marlina; Renny (KHARISMA Tech, 2023)
The main factor that make users comfortable using a website was its performance, websites with long loading times were more likely to be abandoned by visitors. After testing the website of Toko Kerja using Google PageSpeed Insights, there were many opportunities that can be done to improve the performance of the website Toko Kerja, Google PageSpeed Insights was a tool developed by Google to test and analyze the performance of a website on desktops and mobile devices and provide advice to improve performance, accessibility, and SEO. This research aims to analyze the website of Toko Kerja using Google PageSpeed Insights, then if it was below the Google PageSpeed Insights standard, optimization will be carried out to match or be above the standard. This research used quantitative data, which was obtained from the analysis results of the Google PageSpeed Insights tool. The results of the Google PageSpeed Insights analysis were website performance scores using a percent scale and website speed using a time measure. The results show that after making improvements based on Google PageSpeed Insights suggestions, the performance score increased from 85 to 99, the accessibility score increased from 91 to 100, and the SEO score increased from 70 to 80. Based on the research results website Toko Kerja was optimized.